Estimation of enteric methane emission factor in cattle species in Ethiopia using IPCC tier 2 methodology - Million Tadesse; Kefale Getahun; Ulfina Galmessa (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
Aims: The livestock production system contributes to global climate change directly through the production of methane (CH4) from enteric fermentation, CH4 and nitrous oxide (N2O) from manure management. Enteric CH4 emission from livestock is the major contributor to greenhouse gas (GHG) emission from livestock in Ethiopia. National inventory and reporting of enteric CH4 emission in cattle species in Ethiopia are based on default emission factor (tier 1 methodology) developed by Intergovernmental Panel on Climate Change (IPCC). These enteric CH4 emissions are influenced by different factors such as livestock feed characteristics, livestock management, and livestock production and productivity. Hence, its estimation requires accurate data specific to the condition of the livestock production system in the country. The objective of this study was to estimate enteric CH4 emission from cattle species in Ethiopia.  Methodology: Enteric CH4 emission was estimated using IPCC tier 2 methods using input data collected through survey and literature data on livestock and feed characteristics in Ethiopia.  Results: Results indicated that enteric CH4 emission factors among indigenous cattle were 30.27, 18.52, 31.55, 29.82, 32.48, and 12.60 kg per head per year for matured females >2 years old, females 1-2 years, bullocks/oxen, breeding bulls >2 years old, males 1-2 years and calves <1 year's old, respectively. Among crossbred dairy cattle, enteric CH4 emission factors were found to be 36.21, 19.98, 27.90, 25.51, 5.45 kg per head per year for matured females >2 years, females 1-2 years, matured males >2 years, males 1-2 years and calves <1 year's age, respectively. The weighted average CH4 emission factor for indigenous cattle and crossbred dairy cattle were 26 and 30.71kg/head/year, respectively.  Conclusion: Enteric CH4 emission factors for nondairy indigenous and crossbred cattle using IPCC tier 2 methodology were lower when compared to IPCC tier 1 estimate. Our study recommends IPCC tier 2 methodology, for national enteric CH4 emission inventory and reporting for cattle species in Ethiopia. The present study was based on limited survey and published data, uncertainties may have presented with, some of production and performance data. Further research is required to estimate enteric CH4 emission using more detailed cattle production and feed characterization data.